(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The problem of drug abuse is one of the biggest and most dangerous social problems that all countries of the world suffer from, which strive to combat it, because of its health, social and economic damages. A pathological social phenomenon that is driven by many factors, some of which are related to the individual, some to the family, and others to the social structure as a whole, which constitutes a threat to the entity of society.In this context, this study seeks to identify the most important theories that dealt with the interpretation of the phenomenon of drug abuse. Because of its dangerous consequences for individuals, the family, and society, which requires researchers, scholars, and workers in the social field in particular to intensify efforts in order to address this phenomenon and reduce its risks.Where the descriptive approach was adopted, after which some recommendations and proposals were reached to reduce the phenomenon of drug abuse.